Hadrah, Cultural Da'wah, and National Identity in the Indonesia–Malaysia Borderland Community - Dilah Tuah; Yusriadi Yusriadi; Munawar Munawar; Ismail Ruslan; Fahmi Ichwan; Raziki Wildan (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2026)
This article analyses the Hadrah as a form of cultural da‘wah in strengthening Malay-Islamic and Indonesian identity among the border communities of Temajuk (West Kalimantan) and Telok Melano (Sarawak). This study employs a qualitative approach through in-depth interviews and focus group discussions, involving community leaders, religious figures, and members of Hadrah groups in Temajuk and Telok Melano. The findings reveal that Hadrah functions as a strategic medium for strengthening Malay-Islamic identity, social solidarity, and Indonesian nationalism in border communities. Through practices that include zikir, the recitation of the Barzanji, religious study sessions, regular practice, and cross-border performances in Telok Melano—Hadrah reinforces Malay-Islamic identity whilst simultaneously embodying symbols of Indonesian identity. This article emphasises that community-based cultural da’wah can serve as a vital strategy in maintaining social cohesion and national identity in the border regions. This study contributes to da'wah studies by demonstrating how cultural performance serves as a mechanism for identity construction and social cohesion in border societies.